Pengaruh Harga, Produk, dan Promosi Terhadap Minat Beli Pada Toko Online Lazada - Lili Suryati; Lenny Menara Sari Saragih; Fajrillah Fajrillah; Andriasan Sudarso; Altari Meli Gita Tarigan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the effect of price, product, and promotion on buying interest in the Lazada Online Store. The method used in this research is a descriptive quantitative method which is carried out through data collection using questionnaires and statistical test data analysis. The sample taken is the entire population in this study, amounting to 79 respondents. The instruments used are validity and reliability tests. Analysis of the data used is multiple linear regression analysis. The hypothesis test used is a partial t-test, simultaneous F-test, and determination test.The results of the multiple linear regression test are Y = 3,713+0,157X1+0,202X2 +0,512X3+e. The results showed that partially Price, Product, and Promotion had a significant and significant effect on Buying Interest at the Lazada Online Store. And the results of the study simultaneously show that Price, Product, and Promotion have a significant and significant effect on Buying Interest at the Lazada Online Store. The coefficient of determination obtained for the effect of Price, Product, and Promotion has a significant and significant effect on Purchase Interest obtained by 70.90%, while the remaining 29.10% is influenced by other factors not examined in this study